TEKNOLOGI KONSERVASI DAN REHABILITASI TERUMBU KARANG - Santoso, Arif Dwi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Indonesia’s rich supplies of corals and reef fish are endangered by destructive fishing practices. Cyanide and blast fishing are widespread throughout the archipelago even in protected areas. Indonesian reefs are also subject to various pressures from inland activities. Forestation and other land-use changes have increasedsediment discharge onto reefs, and pollution from industrial effluents, sewage, and fertilizer compounds the problem. Cumulatively, these pressures appear to have significantly degraded Indonesia’s reefs over time. Unfortunately, Indonesia has only limited monitoring. Few reefs are regularly studied, making the assessment of condition and change for the country quite difficult. Currently, most monitoringmindicates clearly that reef condition is declining. This article showed the status, biology, and monitoring-rehabilitation method of coral reef in Indonesia.